Clásicos rusos - Roberto M. Gori (Biblioteca selecta de literatura)
Leon Tolstoi : Ana Karenina. Nicolás V. Gogol : Tarás Bulba. F.M. Dostoievski : Los Hermanos Karamozof. Ivan Turguenef : Aguas primaverales. Máximo Gorki : La Madre